Sekerei Mentawai: Keseharian dan Tradisi Pengetahuan Lokal yang Digerus oleh Zaman - Lucky Zamzami (Antropologi Indonesia, 2013)
Based on data from fieldwork in Mentawai, this article discusses the researcher’s interest in traditional medicine actors among the Mentawai people, namely Sekerei. The appeal of a Sekerei is realized through their modest daily lives, despite the effect these days of power from outside and modernity, that has so heavily eroded the local knowledge available. Sekerei are diminishing numbers, and medicinal herb findings are diminishing annually, showing that traditional healers have been split into two parts, namely fixed synergized with traditional natural life, or becoming a very important part in the globalization that is gripping the power of a Sekerei.Key-words: Sekerei, Indigeneus Knowledge, Medicine Herbs